Effect of bone particle size of carp (Cyprinus Carpio) heads in gelatin extraction - Silva, Roberto S. G. da; Bandeira, Sidney F.; Petry, Fabiane C.; Pinto, Luiz Antonio de Almeida (VETOR - Revista de Ciências Exatas e Engenharias, 2012)
Gelatin properties of fish skin are different from mammals gelatins, however literature on gelatin from fish bones is limited. The aim of this study was to evaluate the effect of the bone particle size of common carp (Cyprinus carpio) heads in the yield, melting point and gel strength of gelatin extracted from the bone fraction of carp heads. Four gelatin extractions were carried out for bones particle sizes of 1 and 2 mm, with pH and temperature of each extraction (5.3 – 60°C), (4.4 – 70°C), (3.8 – 80°C) and (3.6 – 85°C), respectively. Higher gelatin yield (4.86%) was found with particle size 1 mm. The higher gel strengths (128 and 131 g) were not significantly different, and they were found in the first extraction with bones particle sizes 1 and 2 mm, respectively. Using particle size of 2 mm, it was possible to obtain higher melting point values, of 28.5°C to the first extraction. All values of yield, melting point and gel strength of gelatin bones were lower than those found by the carp heads gelatin skins.